2021
DOI: 10.1039/d1ta04445a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of GeO2 in enhancing the thermal stability and proton mobility of proton-conducting phosphate glasses

Abstract: In this study, the effect of GeO2 on the thermal stability and proton mobility (μH) of proton-conducting phosphate glasses was experimentally investigated using 22HO1/2−3NaO1/2−(12−x)LaO3/2−xGeO2−63PO5/2 glasses. Increasing glass transition temperature (Tg)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…The activation energy, E a , for proton hopping conduction was determined to be 1.43 eV at T < T g and 1.15-1.85 eV at T � T g from the log(σT)-1/T plot (Figure S3). These E a values are much larger than those of previous protonconducting phosphate glasses (0.7-0.9 eV) with similar proton carrier densities (Figure S4), [20,21] despite the stronger hydrogen bonding in H 5 Si 2 P 9 O 29 glass. Further, the proton conductivity of H 5 Si 2 P 9 O 29 glass was not very high (3 × 10 À 6 S cm À 1 at T g ; 4 × 10 À 4 S cm À 1 at 276 °C).…”
contrasting
confidence: 51%
“…The activation energy, E a , for proton hopping conduction was determined to be 1.43 eV at T < T g and 1.15-1.85 eV at T � T g from the log(σT)-1/T plot (Figure S3). These E a values are much larger than those of previous protonconducting phosphate glasses (0.7-0.9 eV) with similar proton carrier densities (Figure S4), [20,21] despite the stronger hydrogen bonding in H 5 Si 2 P 9 O 29 glass. Further, the proton conductivity of H 5 Si 2 P 9 O 29 glass was not very high (3 × 10 À 6 S cm À 1 at T g ; 4 × 10 À 4 S cm À 1 at 276 °C).…”
contrasting
confidence: 51%
“…To analyze the surfaces of the fresh samples, the glass samples were crushed in a nitrogen atmosphere‐glove box. The crushed samples were then transferred to the spectrometer (vacuum) under nitrogen atmosphere using a gas‐tight transfer vessel (PHI Model 04‐110, ULVAC‐PHI, Inc.) 35 . A charge neutralization system was used to avoid a shift in the spectra due to sample charging that irradiated low‐energy electron and ion beams on the sample surface during measurements.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The crushed samples were then transferred to the spectrometer (vacuum) under nitrogen atmosphere using a gas-tight transfer vessel (PHI Model 04-110, ULVAC-PHI, Inc.). 35 A charge neutralization system was used to avoid a shift in the spectra due to sample charging that irradiated low-energy electron and ion beams on the sample surface during measurements. The binding energies of the spectra were calibrated by using the standard value of the C 1s peak at 284.6 eV.…”
Section: Structural Characterization Of Glassy Samplesmentioning
confidence: 99%
“…We experimentally confirmed that GeO 2 increases T g and m H at T g . 19 The increased T g is attributed to the formation of the P-O-Ge linkages tightly bridging between phosphate chains. The enhanced m H at T g is attributed to the increased ionicity of O-H bonds, resulting in the weakening of O-H bonds and the reduction of the energy barrier for proton dissociation from OH group, arising from the increased covalency of P-O bonds due to the formation of P-O-Ge bonds.…”
Section: Introductionmentioning
confidence: 99%